Revisit Intention Framework: Is It Real that Cultural Contact and Destination Attractiveness Can Have Direct Impact? - Yunfin, Meidarina; Kusumah, Echo Perdana; MS, Mahrinasari; Reniati, Reniati (Jurnal Minds: Manajemen Ide dan Inspirasi, 2023)
This study uses survey responses from 321 Indonesian tourists to examine the connection between cultural contact, destination attractiveness, visitor satisfaction, and the likelihood of a revisit intention to Himpang Lime Habang in the South Bangka regency of the Bangka Belitung province, Indonesia. Two significant findings from this investigation were obtained using Partial Least Squares-Structural Equation Modeling methods. The first finding is the correlation between satisfaction and the likelihood of future visits. Furthermore, a visitor's desire to return is unaffected by the attractiveness of a destination or the amount of cultural contact they have. Even though exposure to local culture and a destination's natural beauty can considerably enhance a visitor's experience, they have little bearing on whether or not someone will return.